2019
DOI: 10.1016/j.engstruct.2018.10.080
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on seismic performance of post-fire reinforced concrete frames

Abstract: To investigate the post-fire seismic behaviour of reinforced concrete (RC) frames with different columnto-beam bending capacity ratios, four specimens were fabricated, which included a strong-beam-weakcolumn frame and a strong-column-weak-beam frame either under room temperature or after being exposed to fire. The fire test was conducted in a furnace chamber, followed by quasi-static tests under a low-frequency cyclic load. The crack patterns, hysteretic loops, plastic hinges, and failure modes were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…CC means concrete with calcareous aggregates, and GC means concrete with granite aggregates. Li et al [26] studied the residual behavior of fire-damaged RC frames and the effect of fire exposure and beam-to-column bending strength ratio on the failure mode; hysteretic loops, load carrying capacity, stiffness degradation, and ductility were also studied. Jiang et al [27] found obvious changes in the shear failure modes of cantilever beams and restrained frame beams after Li et al [26] studied the residual behavior of fire-damaged RC frames and the effect of fire exposure and beam-to-column bending strength ratio on the failure mode; hysteretic loops, load carrying capacity, stiffness degradation, and ductility were also studied.…”
Section: Beamsmentioning
confidence: 99%
“…CC means concrete with calcareous aggregates, and GC means concrete with granite aggregates. Li et al [26] studied the residual behavior of fire-damaged RC frames and the effect of fire exposure and beam-to-column bending strength ratio on the failure mode; hysteretic loops, load carrying capacity, stiffness degradation, and ductility were also studied. Jiang et al [27] found obvious changes in the shear failure modes of cantilever beams and restrained frame beams after Li et al [26] studied the residual behavior of fire-damaged RC frames and the effect of fire exposure and beam-to-column bending strength ratio on the failure mode; hysteretic loops, load carrying capacity, stiffness degradation, and ductility were also studied.…”
Section: Beamsmentioning
confidence: 99%
“…e low cyclic reversed loading test was a widely accepted method to assess the seismic performance of structural members, such as frames, shear walls, and masonry walls [16,33,34]. e specimens were tested in the Disaster Prevention and Mitigation Laboratory of Shandong Jianzhu University, China.…”
Section: Test Setupmentioning
confidence: 99%
“…Concrete is the most widely used building material in the world. However, reinforced concrete (RC) structures might face durability problems (Zhang et al 2017a;Li et al 2019), most of which are caused by the corrosion of steel rebars induced by chloride ions (Mehta 1991). The influence of steel corrosion on an RC structure has the following aspects: First, rusting causes the steel volume to expand, causing the concrete to crack (Rodriguez et al 1994); Second, when a rebar is corroded, the cross-sectional area of the rebar is reduced (Ahmad 2003); Third, the bonding performance of rebar and concrete is decreased by the corrosion (Fang et al 2006).…”
Section: Introductionmentioning
confidence: 99%